Integrated Chemical Processes in Liquid Multiphase Systems From Chemical Reaction to Process Design and Operation - Kraume, Matthias; Enders, Sabine; Drews, Anja; Schomäcker, Reinhard; Engell, Sebastian; Sundmacher, Kai (De Gruyter, 2022)
The essential principles of green chemistry are the use of renewable raw materials, highly efficient catalysts and green solvents linked with energy efficiency and process optimization in real-time. Experts from different fields show, how to examine all levels from the molecular elementary steps up to the design and operation of an entire plant for developing novel and efficient production processes.